Nursing management of a patient with Qi-deficiency type constipation after stroke (1例中风后气虚便秘患者的中医护理体会) - WANG Xuesong (王雪送); ZHOU Yajing (周雅静); YANG Yu (杨宇); LI Chenchen (李陈晨); FAN Yan (范艳); HU Shirong (胡世荣) (中西医结合护理)
This paper summarize the key points of acupoint massage treatment and Traditional Chinese Medicine (TCM) nursing for a patient with Qi-deficiency type constipation after stroke. For patients with Qi-deficiency type constipation after stroke, the degree of Qi-deficiency should be evaluated before treatment. In addition to the application of general therapy, deficiency-supplementing treatment combined with TCM nursing can effectively improve the clinical symptoms of patients with Qi-deficiency type constipation after stroke. (本文总结1例中风后气虚便秘患者经穴推拿治疗与中医护理要点。针对中风后气虚便秘患者, 在治疗前要先评估患者气虚的程度, 治疗中除了需应用通法外还应注意给予补法进行补虚治疗, 配合中医综合护理措施可有效改善患者临床症状并加速康复。)